Electrotonic coupling in the pituitary supports the hypothalamic-pituitary-gonadal axis in a sex specific manner - Göngrich, Christina; García-González, Diego; Le Magueresse, Corentin; Roth, Lena C.; Watanabe, Yasuhito; Burks, Deborah J.; Grinevich, Valéry; Monyer, Hannah (Frontiers in molecular neuroscience, 2016)
Gap junctions are present in many cell types throughout the animal kingdom and allow fast intercellular electrical and chemical communication between neighboring cells. Connexin-36 (Cx36), the major neuronal gap junction protein, synchronizes cellular activity in the brain, but also in other organs. Here we identify a sex-specific role for Cx36 within the hypothalamic-pituitary-gonadal (HPG) axis at the level of the anterior pituitary gland (AP). We show that Cx36 is expressed in gonadotropes of the AP sustaining their synchronous activity. Cx36 ablation affects the entire downstream HPG axis in females, but not in males. We demonstrate that Cx36-mediated coupling between gonadotropes in the AP supports gonadotropin-releasing hormone-induced secretion of luteinizing hormone. Furthermore, we provide evidence for negative feedback regulation of Cx36 expression in the AP by estradiol. We thus, conclude that hormonally-controlled plasticity of gap junction communication at the level of the AP constitutes an additional mechanism affecting female reproduction.
Gesehen am 29.07.2020